Who are bike sharing schemes members and do they travel differently? The case of Lyon's "Velo'v" scheme. (December 2017) - Raux, Charles; Zoubir, Ayman; Geyik, Mirkan
Highlights: Analyze multiday multimodal travel behavior of bike-share registered members. Higher position and proximity to stations have positive effect on annual membership. Bike-sharing is used as other transportation modes for any purpose including commuting. Relevant for "last mile" from/to public transport station. Abstract: This paper analyzes the socio-demographic profile and travel behavior of the "Velo'v" bike-sharing scheme annual members in Lyon (France). This scheme started in 2005 and has now around 350 stations and 4500 bikes in operation, with more than 50, 000 annual members. By the means of an Internet-based survey more than 3000 respondents were described by their detailed socio-demographic profile, their travel means and habits, a one-day activity-travel diary and additionally a seven days activity-travel diary filled by around 700 volunteers. By this way the survey covers all travel modes and day-to-day variations in travel behavior beyond the sole use of shared bike. We analyze with a discrete choice model the socio-demographic and spatial factors affecting the probability of being an annual member of the Velo'v scheme. Then we compare with descriptive statistics their daily travel behavior involving as well bike sharing as other traditional modes to the travel behavior of the general population as given with the latest Household Travel Survey available in the Lyon area (2015). The majority of Velo'v annual members are male, younger and hold higher social positions when compared with the Lyon's general population. An individual higher social position and the residential proximity to stations have both separate and positive effects on the probability of being an annual member of the service. Velo'v members are not captive from public transport, a majority of them have access to a car and they are fully multimodal in their day-to-day travel behavior. Velo'v bikes are used by them for any activity, not necessarily every day, like any other travel mode. The multimodal behavior of Velo'v members shows that Velo'v supply fits especially a demand not satisfied when the public transport station is too distant from home.